ETIKA GURU DAN MURID PERSPEKTIF IMAM ZARNUJI DAN IMAM GHOZALI, TELA’AH KITAB TAKLIM MUTAALLIM DAN KITAB IHYA’ ULUMUDDIN - Tarud Daroini, Moh; Umam, Khoirul (PAI FAI UNHASY Tebuireng Jombang, 2026)
This Article describes teacher and Student Ethics from the Perspective of Imam Zarnuji and Imam Ghazali: An Analysis of the Books Ta'lim al-Muta'allim and Ihya' Ulumuddin. . Research Type: This study is a library research, which is a search for previous research results that are relevant or have a close relationship with the object of research. Conclusion: 1)The conclusion of this study is that teacher ethics according to Imam Zarnuji and Imam Ghazali are those who have broad knowledge, good character, and the ability to guide students effectively, as well as being able to develop students' potential holistically. 2)Meanwhile, student ethics according to Imam Zarnuji and Imam Ghazali are good and polite attitudes in seeking knowledge, including humility, respecting teachers, working hard, and having good and sincere intentiKeywords: Teacher and student ethics from the perspective of Imam Zarnuji and Imam Ghazali, Importance of Teacher and Student Ethics in Improving Education Quality.